Working Capital on Profit (CV X Tours and Travels Case Study in Surabaya) 2013-2018 Period - Enny Istanti; Bramastyo Kusumo Negoro; Achmad Daengs GS (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: to find out and analyze whether working capital variables consisting of liquidity, working capital turnover and accounts receivable turnover affect the profitability of CV. X Tours and Travels and to find out and analyze which of these capital variables has the dominant influence on profitability in CV. X Tours & Travels. Design/methodology/approach: The analysis carried out is quantitative analysis using multiple linear regression to answer the problem formulation and determine the effect of predetermined variables. Findings: . The results of the study obtained the Fcount value of 151.118 with a significance of 0.006, the tcount value of each variable Price tcount -8.706 > ttable 1.97438, liquidity variable tcount 15.235 > ttable 1.97438, and variable Working Capital Turnover tcount 16.860 > ttable 1.97438. Based on the results of research in CV. X Tours and Travels Surabaya of the three independent variables have a simultaneous, partial and significant effect on Profitability. The dominant variable is Working Capital Turnover. Practical implications: Intensifying working capital towards profitability Originality/value: This paper is original Paper type: research sense